Pengaruh Nilai Harga, Motivasi Hedonis, Kebiasaan Dan Daya Tarik Promo Terhadap Minat Menggunakan Mobile Payment OVO - Prasetya, I Gusti Bagus Irvan; Purnamawati, I Gusti Ayu (Jurnal Akuntansi Profesi, 2020)
This study aims to determine the effect of the variable price values, hedonic motivation, habits and attractiveness of promos to the interests of students to use Mobile Payment OVO. The research method that can be used in this study is a quantitative method using primary data in the form of questionnaire data which is then measured through a Likert scale. All Accounting (S1) study program students at Ganesha University of Education were the object of this research. All students majoring in Accounting in the 7th semester are also the population in this study. The purposive sampling method was used as the basis for sampling conducted in this study so that a sample of 134 people was obtained. The distribution of questionnaires which will then be processed using multiple linear regression analysis test using SPSS application version 21 for windows is used to collect all data in this study. The results obtained in this study are: 1) The variable price value has a significant positive effect on student interest using the Mobile payment OVO application, 2) The hedonic motivation variable has a significant positive effect on student interest using the Mobile payment OVO application, 3) The custom variable has a significant positive effect on the student interest in using the Mobile payment OVO application, and 4) The variable attractiveness of the promo has a significant positive effect on the interest in using the Mobile payment OVO application